-54=c-83

Simple and best practice solution for -54=c-83 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -54=c-83 equation:



-54=c-83
We move all terms to the left:
-54-(c-83)=0
We get rid of parentheses
-c+83-54=0
We add all the numbers together, and all the variables
-1c+29=0
We move all terms containing c to the left, all other terms to the right
-c=-29
c=-29/-1
c=+29

See similar equations:

| 22x+3=48 | | -16-6g+17=-15g+10 | | x-3.4=-4.5 | | 5(x +4)=20 | | 10g=15 | | (1.5c+4)=-1 | | 19+4.5h=8.00+5.75h | | -3(4n-2)=-2(7+7n) | | 17×z=340 | | 18d+4=19d | | H(t)=-4.9t+8t+1 | | 8a^2-7=0 | | x-3x=123 | | 2x+.3=5x+1.3 | | X^2-6y-7=0 | | 215-v=128 | | 17-12y=-11y+4 | | 2(7v-4)+2(v-7)=-6v-3v | | 2,3x=-1 | | 13x-80=89 | | 10r-6=9r | | -1/6x=1 | | 9+b=-9-b | | 9x+12x+12=180 | | (4x+8)/12=0 | | 13+11r=2 | | 13=6+p | | -10-6z=10-9z+10 | | -35=-y | | 186=-x+37 | | 2(5k-13)=44 | | 3x-0.45833333333=-1+1/6 |

Equations solver categories